Analisis kotribusi mahasiswa terhadap pertumbuhan ekonomi sektor UMKM di wilayah kampus: Studi kasus pada mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang dan pelaku UMKM di sekitarnya - Udin, Muhammad Muti (Maliki Interdisciplinary Journal, 2023)
The recovery of the Micro, Small, and Medium Enterprises (MSME) sector is important in addressing the negative impacts of economic crises, including the pandemic. The contribution of students to the recovery of the MSME sector is a relevant aspect to be researched. This study aims to analyze the contribution of students to the economic recovery of the MSME sector in the campus area, with a focus on a case study of students at the State Islamic University (UIN) Malang. Students have the potential to provide innovative ideas, high energy, as well as access to continuously evolving resources and knowledge. Involving students in efforts to recover the MSME sector brings dual benefits, both for the students and the MSMEs in the campus area. This research uses a qualitative approach with interviews conducted with students from various faculties and levels at UIN Malang. The results of this study are expected to provide a better understanding of the role and contribution of students to the economic recovery of the MSME sector in the campus area, as well as serve as a basis for policy development and programs that actively involve students in economic recovery efforts and MSME development.